2008
DOI: 10.1515/znc-2008-3-423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interferons on the Repair of UV-Damaged DNA

Abstract: The capacity for nucleotide excision repair of a normal (WISH) and three tumour (MCF-7, HeLa, Namalva) cell lines treated with human recombinant interferons (hrIFN-α and hrIFN-γ) was compared by the host cell reactivation assay. The cells were transfected with in vitro UV-damaged plasmid DNA (pEGFP-N1). The repair capacity was determined by measuring the fluorescence intensity of the expressed marker protein in total cell lysates. The correlation between the interferon-induced NO content and the suppressive ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It was shown, that both types of interferon (IFN-α and IFN-γ) have an inhibiting effect on DNA repair in both cell lines tested. DNA repair suppression by IFN-α was much more pronounced than that caused by IFN-γ (Tsoncheva et al, 2008). In summary, using two different test systems, we have now established that human interferons possess a strong inhibitory effect on repair of UVinduced damage of DNA.…”
Section: Resultsmentioning
confidence: 77%
“…It was shown, that both types of interferon (IFN-α and IFN-γ) have an inhibiting effect on DNA repair in both cell lines tested. DNA repair suppression by IFN-α was much more pronounced than that caused by IFN-γ (Tsoncheva et al, 2008). In summary, using two different test systems, we have now established that human interferons possess a strong inhibitory effect on repair of UVinduced damage of DNA.…”
Section: Resultsmentioning
confidence: 77%
“…The nonsignificant change compared to the positive control in the level of micronuclei in bone marrow cells when using both gentabiferon-B and biferon-B where cytogenetic instability was induced by MMC indicates that there are no antimutagenic properties of gentabiferon-B. The presented data may be explained by the ability of interferons to exhibit antimutagenic activity, such as DNA repair, depending on the type of interferon and the genotype of the cell (13,25).…”
Section: Discussionmentioning
confidence: 89%
“…Overall, this indicates several abnormalities in the DRC of pre-aHCT patient samples, which raises the question of the ability of such samples to reliably represent an individual’s repair capacity. It has been suggested that DRC in lymphocytes of cancer patients might be greatly affected by the general inflammation associated with the disease [ 57 59 ] or possibly by the cancer treatment itself. Consistent with that hypothesis, we had observed that DSB repair measurements by host-cell reactivation assays, even in lymphocytes from healthy individuals, could be influenced by factors in the environment of the cells, such as the presence of reactive oxygen species [ 34 ].…”
Section: Discussionmentioning
confidence: 99%